Maturation of human dendritic cells with Saccharomyces cerevisiae (yeast) reduces the number and function of regulatory T cells and enhances the ratio of antigen-specific effectors to regulatory T cells - Cereda, Vittore (2011)
We compared the effects of yeast-treated human dendritic cells (DCs) with CD40L-matured human DCs for the induction of effector cells and the number and functionality of CD4(+)CD25(+)CD127(−) FoxP3(+) regulatory T cells (Tregs). DCs were treated with yeast or CD40L and cocultured with isolated autologous CD4(+) T cells. CD4(+)CD25(+)CD127(−) T cells isolated from the coculture of CD4(+) T cells plus yeast-treated DCs (yeast coculture) had a lower expression of FoxP3 and decreased suppressive function compared to CD4(+)CD25(+)CD127(−) T cells isolated from the coculture of CD4(+) T cells plus CD40L-treated DCs (CD40L coculture). Also, compared to the CD40L coculture, the yeast coculture showed increases in the ratio of CD4(+)CD25(+) activated T cells to Tregs and in the production of Th1-related cytokines (IL-2, TNF-α, IFN-γ) and IL-6. In addition, yeast-treated DCs used as antigen-presenting cells (APCs) incubated with the tumor antigen CEA enhanced the proliferation of CEA-specific CD4(+) T cells compared to the use of CD40L-matured DCs used as APCs. This is the first study to report on the role of yeast-treated/matured human DCs in reducing Treg frequency and functionality and in enhancing effector to Treg ratios. These results provide an additional rationale for the use of yeast as a vector in cancer vaccines.